Maternal warming influences reproductive frequency, but not hatchling phenotypes in a multiple-clutched oviparous lizard. (May 2018) - Lu, Hong-Liang; Wang, Jie; Xu, Da-De; Dang, Wei
Abstract: The understanding of life-history responses to increased temperature is helpful for evaluating the potential of species for tackling future climate change. Herein, adult southern grass lizards, Takydromus sexlineatus, were maintained under two thermal regimes simulating current thermal environment and a 4 °C warming scenario to determine the effects of experimental warming on female reproduction and offspring phenotypes. Experimental warming caused females to oviposit earlier and more frequently; however, it did not affect other reproductive traits, including clutch size, egg mass and clutch mass. Accelerated embryonic development and energy accumulation rate might have occurred in warmed females. Maternal warming appeared to increase early embryonic mortality, but did not shift hatchling size and locomotor performance. Embryos of oviparous lizards might be more vulnerable to climate change at early stages than at later stages. The impacts of climate change in oviparous lizards might be adverse in the longer term because of the shift in pre-ovipositional embryo viability, which possibly led to a decreased number of hatchlings. Highlights: Experimental warming caused female grass lizards to oviposit earlier and more frequently. Maternal warming appeared to increase early embryonic mortality, but did not influence hatchling traits. Early stage embryos of oviparous species may be relatively vulnerable to climate change.